2016
DOI: 10.1093/cercor/bhw082
|View full text |Cite
|
Sign up to set email alerts
|

The Disconnected Brain and Executive Function Decline in Aging

Abstract: Higher order speeded cognitive abilities depend on efficient coordination of activity across the brain, rendering them vulnerable to age reductions in structural and functional brain connectivity. The concept of "disconnected aging" has been invoked, suggesting that degeneration of connections between distant brain regions cause cognitive reductions. However, it has not been shown that changes in cognitive functions over time can be explained by simultaneous changes in brain connectivity. We followed 119 young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 87 publications
15
146
0
Order By: Relevance
“…However, the energy probabilities of the visual network declined, while the energy probabilities of the default, frontoparietal, and limbic networks decreased further. This result may be consistent with the further enhanced heterogeneity of whole-brain functional subsystems [60][61][62][63][64][65]. The values of EP in the brain regions of the frontoparietal network increased slightly.…”
Section: The Orderness Variability Of Functional Subsystems With Agesupporting
confidence: 83%
“…However, the energy probabilities of the visual network declined, while the energy probabilities of the default, frontoparietal, and limbic networks decreased further. This result may be consistent with the further enhanced heterogeneity of whole-brain functional subsystems [60][61][62][63][64][65]. The values of EP in the brain regions of the frontoparietal network increased slightly.…”
Section: The Orderness Variability Of Functional Subsystems With Agesupporting
confidence: 83%
“…To assess the comparability of the results with data from the now more commonly used 3T scanners and longer scanning sequences, 44 young participants were scanned both on the 1.5T scanner with 100 volumes, and on a 3T scanner with 150 volumes on the same day. Previously reported validation analyses (Fjell et al, 2016a) demonstrated excellent convergence between network structure detected across 1.5 and 3T scanners and 100 vs. 150 volumes…”
Section: Methodsmentioning
confidence: 77%
“…Normal age-related structural and functional connectivity alterations independent of decision making are not the focus of the present study and have already been reported and reviewed in the literature elsewhere (Andrews-Hanna et al, 2007; Ferreira and Busatto, 2013; Antonenko and Flöel, 2014; Bennett and Madden, 2014; Dennis and Thompson, 2014; Sexton et al, 2014; Sala-Llonch et al, 2015; Ferreira et al, 2016; Fjell et al, 2016). In summary, these studies showed that there is a normal age-related decline in structural as well as functional connectivity strength that is not uniformly distributed throughout the brain, i.e., the magnitude of connectivity reductions differs between brain regions.…”
Section: Introductionmentioning
confidence: 78%